KONCEPTUALIZACJA PRZESTRZENI I CZASOWNIKI RUCHU W JĘZYKU POLSKIM I FRANCUSKIM JAKO OBCYM - Paprocka-Piotrowska, Urszula (Neofilolog, 2019)
The following text presents part of a trans-lingual research project which aims at the comparison of the acquisition of French and Polish as second languages. The empirical research presented below attempts to answer questions about the extent of language categorisation (semantic/syntactic structures), characteristics of the mother tongue, and influences of the representation of the objective world in the moment when an adult who is learning a (typologically different) foreign language starts to use it in actual communication.